Tumble on the Tendency towards the Emerging Spiritualities: the Evolution of the Youth Narrative of the Holy (Case Study of Students Engaging in New Spiritualities in Isfahan City) - Ali ghanbaribarzain; Shapour Salmanvandi; simin barfei (توسعه اجتماعی)
The present study deals with the qualitative study of young people's tendency toward emerging spirituality and their narrative as a sacred thing. The main question of this study is that how does it affect the spirituality of the new religions of religiosity, and how do they differ in their religiosity before and after encountering the emerging spiritualities? The statistical population of this research is the city of Isfahan. The research sample was selected using the narratives reproduced by 21 converts to the newly created spiritualities. Data were analyzed using thematic analysis method. The target group of the study was between the ages of 22 and 34. The result of this research shows that some of the forms of religious evolution of the individuals studied in the face of the emerging spirituality can be summarized as follows: the relative degradation of the system of beliefs, the reduction of guilty feelings, relativistic and conceptual beliefs rather than dogmatic beliefs, emphasis on love and presence Instead of emphasizing God's wrath and power, moving from the sacramental religious ethics to a tendency towards transcendental ethics, overcoming the moral endeavor of rhetorical endeavors, the imitation of mythology to individualistic faith - the affection, the increase of tolerance and tolerance in the face of other tendencies Belief.